Not EF skills but play with real toys prevents screen time tantrums in children - Gavrilova, Margarita; Veraksa, Nikolay (Frontiers in Psychology, 2024)
Limiting children's screen time has become a new challenge for parenting. Due to the high attractiveness of media, many children experience painful screen time transitions to other activities. It is important to understand which factors reinforce a child's negative reactions and which factors make it easier to enforce screen time limits. This can help parents and childhood educators prevent screen time tantrums or enrich children's non-digital activities, making them attractive alternatives to the media. Based on theoretical insights into the coping mechanisms of frustration and anger in preschool children, this study aims to examine the impact of such factors as executive functions skills, family activities, and children's play with real toys on screen time tantrums. Sample included 654 caregiver-child pairs participated in the study (M children age = 70.3 months, SD = 4.02). Playing with real toys had a preventive effect on screen time tantrums in children. The findings suggest that creating conditions and supporting children's play could help children avoid painful screen time transitions.